Analysis of the Implementation of DSN-MUI Fatwa Number 25/DSN-MUI/III/2002 Concerning Rahn (Pawn) and Financing Restructuring Solutions at Pegadaian Syariah Binjai - Sasna Safitri; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study aims to analyze the implementation of DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 concerning rahn (Islamic pawn) and to examine financing restructuring solutions at Pegadaian Syariah Binjai. Rahn is one of the rapidly growing Islamic financing products, as it offers an alternative mechanism that is free from usury and aligned with Sharia principles. However, in practice, there are still potential inconsistencies, particularly in the determination of ujrah (service fees) and the handling of problematic financing. This research employs a descriptive qualitative method with a field research approach. Data were collected through interviews with Pegadaian staff and customers, as well as through relevant documentation. The data analysis techniques include data reduction, data display, and conclusion drawing. The results indicate that the implementation of the DSN-MUI fatwa at Pegadaian Syariah Binjai is generally in accordance with Sharia principles, especially in terms of rahn contracts and the prohibition of usury. However, there are indications that the determination of ujrah is not entirely independent of the loan value. In addition, problematic financing is mainly caused by customers' economic conditions and their limited understanding of the contract. To address these issues, the institution applies financing restructuring mechanisms such as rescheduling, reconditioning, and restructuring, which are considered effective and remain compliant with Sharia principles.